Phosphor, fluorescent member and light-emitting module
Patent Information
- Application Number
- JP2021118918
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-29
- Filing Date
- 2021-07-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-07-19
AI Technical Summary
【0020】 本発明によれば、新規な蛍光体を提供できる。
Smart Images

Figure 0007637592000003 
Figure 0007637592000004 
Figure 0007637592000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a phosphor. [Background technology]
[0002] Conventionally, white light sources that combine YAG phosphors and blue LEDs have been widely known. However, as light sources become more bright, thermal quenching occurs due to heat concentration caused by wavelength conversion (Stokes loss) in the YAG phosphor, resulting in a decrease in the efficiency of the white light source. To address this issue, we developed BaY, a solid solution of Ba and Si in YAG phosphor. 1.92 Al4SiO 12 :Ce 0.08 This phosphor is different from the conventional YAG phosphor (Y3Al5O 12 It has better temperature characteristics than ZnO (Ce), and when heated from 25°C to 200°C, the luminescence intensity retention rate is 91.5%, and it is less likely to suffer from thermal quenching. [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Haipeng Ji et al., "New Y2BaAl4SiO12:Ce3+ yellow microcrystal-glass powder phosphor with high thermal emission stability", Journal of Materials Chemistry C, 2016, 4, pp.9872-9878 Summary of the Invention [Problem to be solved by the invention]
[0004] However, the aforementioned BaY 1.92 Al4SiO 12 :Ce 0.08There are limitations to the chromaticity range that can be achieved with the yellow phosphor represented by [formula]. Therefore, there are also limitations to the chromaticity range that can be achieved as a white light source by combining this yellow phosphor and a blue LED.
[0005] The present invention has been made in view of such circumstances, and one of its objectives is to provide a novel phosphor.
Means for Solving the Problems
[0006] To solve the above problems, the phosphor of one aspect of the present invention has a general formula of M a Y 3-a-b Al 5-a / 2 P a / 2 O 12 :Ce b (However, M represents at least one element selected from the group consisting of Ba, Sr, Ca, and Mg. a satisfies 0 < a ≤ 1.5, and b satisfies 0 < b ≤ 0.12.)
[0007] According to this aspect, a novel phosphor with good emission characteristics and temperature characteristics can be realized.
[0008] The crystal structure may be of the garnet type.
[0009] It may be excited by blue light with a peak wavelength in the range of 430 - 480 nm and emit yellow light with a dominant wavelength in the range of 567 - 572 nm. Thereby, a novel yellow phosphor can be realized.
[0010] It may be excited by blue light with a peak wavelength in the range of 430 - 480 nm and emit light satisfying 0.414 ≤ cx ≤ 0.453 and 0.532 ≤ cy ≤ 0.558 for the chromaticity coordinates (cx, cy). Thereby, for example, a white light source can be realized in combination with a light-emitting element that emits blue light with a peak wavelength in the range of 430 - 480 nm.
[0011] Another aspect of the present invention is a fluorescent member. The fluorescent member may include a phosphor powder that is a powder of the above-mentioned phosphor, and a thermally conductive powder that is a powder of a material having a thermal conductivity higher than that of the phosphor.
[0012] According to this embodiment, the heat dissipation property of the fluorescent member can be improved.
[0013] The volume ratio of the phosphor powder to the thermally conductive powder may be 90: 10 to 60: 40. This can improve the heat dissipation property of the fluorescent member and enhance the light emitting performance of the fluorescent member.
[0014] The phosphor powder may absorb light with a peak wavelength of 450 nm, the thickness of the fluorescent member may be 0.12 to 0.30 mm, and the transmittance of the fluorescent member to light with a wavelength of 550 to 600 nm may be 70% or more, thereby realizing light suitable for a desired application (for example, a headlamp) while increasing the mechanical strength of the fluorescent member.
[0015] The phosphor powder absorbs blue light with a peak wavelength of 450 nm, and the fluorescent member may have an absorptivity of 75 to 85% for blue light, thereby achieving light suitable for a desired application (for example, a headlamp).
[0016] The fluorescent member may include a resin that is transparent to visible light and a phosphor encapsulated in the resin. The phosphor may be contained in the resin at 0.1 to 30 vol %, and the thickness of the fluorescent member may be 0.01 to 5 mm. This makes it possible to realize a light emitting module that achieves a desired luminous efficiency and emits light with a chromaticity in a desired range.
[0017] Another aspect of the present invention is a light-emitting module. The light-emitting module includes an LED that emits blue light with a peak wavelength in the range of 430 to 480 nm, and an optical wavelength conversion layer that is excited by the blue light emitted by the LED and contains the above-mentioned fluorescent material and emits yellow light. The light emitted by mixing the blue light and the yellow light has a chromaticity in the range surrounded by chromaticity coordinates (cx, cy) = (0.311, 0.339), (0.313, 0.342), (0.331, 0.354), (0.331, 0.338), (0.319, 0.315), and (0.311, 0.309).
[0018] According to this embodiment, a white light source suitable for a specific application (for example, a vehicle headlamp) can be realized.
[0019] Any combination of the above components, and any conversion of the expression of the present invention between a manufacturing method, a device such as a lamp or lighting, a light-emitting module, a light source, etc. are also valid as aspects of the present invention. Effect of the Invention
[0020] According to the present invention, a novel phosphor can be provided. [Brief description of the drawings]
[0021] [Figure 1] This is a chromaticity diagram (CIE1931) showing the chromaticity of the emitted color of a conventional yellow phosphor and a blue LED. [Diagram 2] FIG. 4 is a diagram for explaining a range of dominant wavelengths targeted by a yellow phosphor according to the present embodiment. [Diagram 3] FIG. 4 is a diagram showing the relationship between the amount of P contained in the yellow phosphor and the dominant wavelength in the yellow phosphor according to the present embodiment. [Figure 4] FIG. 1 is a graph showing the relationship between the amount of P charged and the luminescence intensity. [Diagram 5] FIG. 1 is a graph showing the relationship between the amount of P charged and the temperature characteristics (luminous intensity maintenance rate). [Figure 6] 1 is a schematic diagram of a light-emitting module according to an embodiment of the present invention; [Figure 7]It is a diagram for explaining the relationship between the chromaticity of the emission color of the light-emitting module according to Examples 11 to 14 and the concentration of the yellow phosphor contained therein.
Embodiment for Carrying Out the Invention
[0022] Hereinafter, the present invention will be described with reference to the drawings based on preferred embodiments. The same or equivalent components, members, and processes shown in each drawing are denoted by the same reference numerals, and repeated explanations will be omitted as appropriate. Further, the embodiments are illustrative and not restrictive of the invention, and all features and combinations thereof described in the embodiments are not necessarily essential to the invention.
[0023] [Phosphor] The phosphor according to the present embodiment is a phosphor that is efficiently excited by blue light and emits light. Specifically, it shows strong excitation by blue light having a peak wavelength in the range of 430 to 480 nm and emits yellow light having a dominant wavelength in the range of 567 to 572 nm. Further, the phosphor according to the present embodiment has a garnet-type crystal structure, and realizes yellow emission by doping an activator such as Ce 3+ ions.
[0024] Next, the phosphor according to the present embodiment will be described in detail. The phosphor according to the present embodiment has a general formula of M a Y 3-a-b Al 5-a / 2 P a / 2 O 12 :Ce b (However, M represents at least one element selected from the group consisting of alkaline earth metals Ba, Sr, Ca, and Mg. a satisfies 0 < a < 1.5, and b satisfies 0 < b < 0.12.) It is represented by. The background of the present inventors' conception of this phosphor is as follows.
[0025] (1) Dominant wavelength shift Cerium (Ce 3+In the crystal, Ce forms a dodecahedral structure factor (Ce site) with oxygen (O). At that time, the Ce site shares edges with SiO4 tetrahedrons (side length 1.60 Å) or AlO4 tetrahedrons (side length 1.74 Å) at two points. By replacing the Si (ionic radius 0.26 Å) of this SiO4 tetrahedron with phosphorus (P) (ionic radius 0.17 Å) which has a smaller ionic radius than Si, a PO4 tetrahedron (side length 1.48 Å) smaller than the SiO4 tetrahedron is generated. As a result, the edge shared with the Ce site shrinks, causing distortion in the Ce site, and the crystal field energy increases, which led to the idea that it may be possible to realize a phosphor whose dominant wavelength is shifted to the longer wavelength side.
[0026] FIG. 1 is a chromaticity diagram (CIE1931) showing the chromaticity of a conventional yellow phosphor and the chromaticity of the emitted color of a blue LED. Point C1 in FIG. 1 corresponds to a known phosphor (BaY 1.92 Al4SiO 12 :Ce 0.08 ) and the dominant wavelength of this known phosphor is 566.3 nm. Meanwhile, point C2 is the chromaticity coordinate of an example of a blue LED whose peak wavelength is in the range of 430 to 480 nm.
[0027] Moreover, range R1 is a chromaticity range defined as a white light for a specific purpose (vehicle headlights). Specifically, range R1 is a range surrounded by chromaticity coordinates (cx, cy) = (0.311, 0.339), (0.313, 0.342), (0.331, 0.354), (0.331, 0.338), (0.319, 0.315), and (0.311, 0.309).
[0028] The mixed light obtained by combining the yellow light of a known phosphor with the blue light of an LED has a chromaticity on the line connecting points C1 and C2. Therefore, as shown in FIG. 1, if the dominant wavelength of the yellow light is on the long wavelength side, it is not possible to realize white light falling within range R1 unless the blue LED is changed. Therefore, a phosphor whose dominant wavelength is shifted to the long wavelength side compared to conventional yellow phosphors, such as the yellow light phosphor of the present invention, is required.
[0029] (2) Suppression of thermal quenching The cause of thermal quenching is thought to be the increase in lattice vibration when the temperature rises. In more detail, the excitation energy absorbed by Ce is absorbed by the vibration of oxygen ions coordinated to Ce due to the fluctuation (expansion-contraction) of the coordination structure of Ce, which is a luminescent element, and is deactivated.
[0030] In the crystals of conventional phosphors in which Ba and Si are dissolved in a solid solution in a YAG phosphor, the AlO4 tetrahedron formed by Al and O and the SiO4 tetrahedron formed by Si and O have equivalent bonds between Al and O (Al-O) and Si and O (Si-O), so the positions of Al and Si are fixed and form a strong tetrahedral unit. This tetrahedral unit vibrates as a strong tetrahedron when the temperature rises, so the Ce sites sharing the edges are subjected to large lattice vibrations.
[0031] On the other hand, in the PO4 tetrahedron formed by P and O, one of the bonds (PO) with four O coordinated to P forms a double bond, so the position of P is not equivalent to the four O. Therefore, P can vibrate (change position) in the PO4 tetrahedron. As a result, the influence of thermal vibration on the Ce site sharing the edge is reduced, and the present inventors have conceived the possibility of suppressing thermal quenching.
[0032] The present invention will be described in more detail below with reference to examples. However, the following descriptions of the raw materials, manufacturing method, and chemical composition of the phosphor do not limit the embodiments of the phosphor of the present invention in any way.
[0033] Example 1 The phosphor according to Example 1 is Ba 0.80 Y 2.14 Al 4.60 P 0.40 :Ce 3+ 0.06The phosphor according to Example 1 is manufactured by the following method. First, powder raw materials of BaCO3 (99.9%: manufactured by Kanto Chemical Co., Ltd.), Y2O3 (99.9%: manufactured by Kojundo Chemical Laboratory Co., Ltd.), CeO2 (99.99%: manufactured by Kojundo Chemical Laboratory Co., Ltd.), α-Al2O3 (99.99%: manufactured by Kojundo Chemical Laboratory Co., Ltd.), and AlPO4 (manufactured by Kojundo Chemical Laboratory Co., Ltd.) are prepared. Then, each powder raw material is weighed so that the molar ratios are Ba=0.80, Y=2.14, Al=4.60, P=0.40, and Ce=0.06.
[0034] BaF2 (99%: manufactured by Kojundo Chemical Laboratory Co., Ltd.) was weighed as flux at 5 wt% of the total weight of the powdered raw materials, and was mixed with the powdered raw materials and mixed uniformly in a mortar. It was then placed in an alumina crucible (SSA-S B1: manufactured by Nikkato Co., Ltd.) and heated at 1550°C for 4 hours in a reducing atmosphere (H2:N2 = 5 / 95 (vol ratio)) and sintered. After cooling to room temperature, it was crushed in a mortar and the luminescence characteristics of the phosphor excited by light with a wavelength of 460 nm was measured using a spectrophotometer (FP-8500: manufactured by JASCO Corporation).
[0035] As a result, the dominant wavelength of the phosphor according to Example 1 was 569.0 nm, and the emission intensity was 1.15 times that of a comparative example not containing P, which will be described later. As for the temperature characteristics, the emission intensity maintenance rate when the temperature was raised from 25° C. to 200° C. was evaluated and found to be 95.0%.
[0036] The results of the light emitting characteristics and temperature characteristics of the phosphors according to the respective Examples and Comparative Examples are summarized in Table 1. In Table 1, the phosphors are listed in order starting from Example 8, which had the smallest amount of P added.
[0037] [Table 1]
[0038] Example 2 The phosphor according to Example 2 is Ba 1.00 Y 1.94 Al 4.50 P 0.50 :Ce3+ 0.06 The phosphor was produced under the same conditions as in Example 1, except that the raw material powders similar to those in Example 1 were weighed to have molar ratios of Ba=1.00, Y=1.94, Al=4.50, P=0.50, and Ce=0.06, and the luminescence characteristics and temperature characteristics were evaluated.
[0039] Example 3 The phosphor according to Example 3 is Ba 0.60 Y 2.34 Al 4.70 P 0.30 :Ce 3+ 0.06 The phosphor was produced under the same conditions as in Example 1, except that the raw material powders similar to those in Example 1 were weighed out to have molar ratios of Ba=0.60, Y=2.34, Al=4.70, P=0.30, and Ce=0.06, and the luminescence characteristics and temperature characteristics were evaluated.
[0040] Example 4 The phosphor according to Example 4 is Ba 0.50 Y 2.44 Al 4.75 P 0.25 :Ce 3+ 0.06 The phosphor was produced under the same conditions as in Example 1, except that the raw material powders similar to those in Example 1 were weighed to have molar ratios of Ba=0.50, Y=2.44, Al=4.75, P=0.25, and Ce=0.06, and the luminescence characteristics and temperature characteristics were evaluated.
[0041] Example 5 The phosphor according to Example 5 is Ba 0.20 Y 2.77 Al 4.90 P 0.10 :Ce 3+ 0.03 The phosphor was produced under the same conditions as in Example 1, except that the raw material powders similar to those in Example 1 were weighed to have molar ratios of Ba=0.20, Y=2.77, Al=4.90, P=0.10, and Ce=0.03, and the luminescence characteristics and temperature characteristics were evaluated.
[0042] Example 6 The phosphor according to Example 6 is Ba 1.20 Y 1.72 Al 4.40 P 0.60 :Ce 3+ 0.08 The phosphor was produced under the same conditions as in Example 1, except that the raw material powders similar to those in Example 1 were weighed to have molar ratios of Ba=1.20, Y=1.72, Al=4.40, P=0.60, and Ce=0.08, and the luminescence characteristics and temperature characteristics were evaluated.
[0043] Example 7 The phosphor according to Example 7 is Ba 1.30 Y 1.60 Al 4.35 P 0.65 :Ce 3+ 0.10 The phosphor was produced under the same conditions as in Example 1, except that the raw material powders similar to those in Example 1 were weighed to have molar ratios of Ba=1.30, Y=1.60, Al=4.35, P=0.65, and Ce=0.10, and the luminescence characteristics and temperature characteristics were evaluated.
[0044] Example 8 The phosphor according to Example 8 is Ba 0.10 Y 2.87 Al 4.95 P 0.05 :Ce 3+ 0.03 The phosphor was produced under the same conditions as in Example 1, except that the raw material powders were weighed out in the following molar ratios: Ba=0.10, Y=2.87, Al=4.95, P=0.05, and Ce=0.03, and the luminescence characteristics were evaluated. The results of the luminescence characteristics and temperature characteristics are shown in Table 1.
[0045] Example 9 The phosphor according to Example 9 is Ba 1.50 Y 1.38 Al 4.25 P 0.75 :Ce 3+0.12 The phosphor was produced under the same conditions as in Example 1, except that the raw material powders similar to those in Example 1 were weighed to have molar ratios of Ba=1.50, Y=1.38, Al=4.25, P=0.75, and Ce=0.12, and the luminescence characteristics and temperature characteristics were evaluated.
[0046] Example 10 The phosphor according to Example 10 is Ba 1.10 Y 1.84 Al 4.45 P 0.55 :Ce 3+ 0.06 The phosphor was produced under the same conditions as in Example 1, except that the raw material powders similar to those in Example 1 were weighed to have molar ratios of Ba=1.10, Y=1.84, Al=4.45, P=0.55, and Ce=0.06, and the luminescence characteristics and temperature characteristics were evaluated.
[0047] (Comparative Example) The phosphor according to the comparative example is Ba 1.00 Y 1.92 Al 4.00 S 1.00 :Ce 3+ 0.08 The phosphor according to the comparative example is manufactured by the following method. First, powder raw materials of BaCO3 (99.9%: manufactured by Kanto Chemical Co., Ltd.), Y2O3 (99.9%: manufactured by Kojundo Chemical Laboratory Co., Ltd.), CeO2 (99.99%: manufactured by Kojundo Chemical Laboratory Co., Ltd.), α-Al2O3 (99.99%: manufactured by Kojundo Chemical Laboratory Co., Ltd.), and SiO2 (99.9%: manufactured by Tokuyama Corporation) are prepared. Then, each powder raw material is weighed so that the molar ratios are Ba=1.00, Y=1.92, Al=4.00, Si=1.00, and Ce=0.08. Thereafter, phosphors were manufactured under the same conditions as in Example 1, and the luminescence characteristics and temperature characteristics were evaluated.
[0048] 2 is a diagram for explaining the range of dominant wavelengths targeted by the yellow phosphor according to the present embodiment. In order to realize the chromaticity range defined as the white light of a vehicle headlight in combination with a blue LED, the yellow phosphor according to the present embodiment requires that a straight line connecting the chromaticity (cx2, cy2) of the blue LED and the chromaticity (cx1, cy1) of the yellow phosphor pass through the range R1.
[0049] According to the inventors' studies, when a line connecting the chromaticity (cx2, cy2) of the blue LED at point C2 and the chromaticity (cx1', cy1') of the yellow phosphor at point C1' meets at the upper part of chromaticity range R1, the dominant wavelength is 567.4 nm. Similarly, when a line connecting the chromaticity (cx2, cy2) of the blue LED at point C2 and the chromaticity (cx1", cy1") of the yellow phosphor at point C1" meets at the lower part of chromaticity range R1, the dominant wavelength is 570.6 nm.
[0050] Therefore, the yellow phosphor according to this embodiment preferably has a dominant wavelength in the range of 567 to 572 nm, and more preferably has a dominant wavelength in the range of 567.4 to 570.6 nm.
[0051] FIG. 3 is a diagram showing the relationship between the amount of P and the dominant wavelength in the yellow phosphor according to the present embodiment. FIG. 3 shows Examples 1 to 4 in which the amount of Ce is the same, 0.06 mol. As shown in Table 1, all the yellow phosphors in Examples 1 to 10 have a dominant wavelength shifted to the longer wavelength side than 566.3 nm, which is the dominant wavelength of a known yellow phosphor. The dominant wavelength of the yellow phosphors in each Example except Example 8 is in the range of 567 to 572 nm. The dominant wavelength of the yellow phosphors in each Example except Examples 8 and 9 is in the range of 567.4 to 570.6 nm.
[0052] That is, the general formula M of the yellow phosphor according to this embodiment a Y 3-a-b Al 5-a / 2 P a / 2 O12 :Ce b In this case, a is preferably in the range of 0 < a ≤ 1.5, more preferably in the range of 0.10 ≤ a ≤ 1.50, and still more preferably in the range of 0.20 ≤ a ≤ 1.30. Also, b is preferably in the range of 0 < b ≤ 0.12.
[0053] Figure 4 is a diagram showing the relationship between the charged amount of P and the emission intensity. Figure 5 is a diagram showing the relationship between the charged amount of P and the temperature characteristics (emission intensity maintenance rate). As shown in Figure 4, when the charged amount of P is in the range of 0.20 to 0.50 mol, the yellow phosphor according to this embodiment has an emission intensity improved by about 10 to 15% compared with the comparative example. That is, focusing on the emission intensity, a in the general formula representing the yellow phosphor according to this embodiment is preferably in the range of 0.40 ≤ a ≤ 1.00.
[0054] Also, as shown in Figure 5 and Table 1, considering the decrease in temperature characteristics in Example 7 and Example 9 (the emission intensity at 200 °C decreases to 0.88 to 0.90 times the emission intensity at 25 °C), a in the general formula representing the yellow phosphor according to this embodiment is preferably in the range of 0.10 ≤ a ≤ 1.20, and b is preferably in the range of 0.03 ≤ b < 0.10. Preferably, if a is in the range of 0.50 ≤ a ≤ 0.80, an emission intensity maintenance rate of about 95% can be achieved.
[0055] Thus, the yellow phosphor according to this embodiment is a novel phosphor with good emission characteristics and temperature characteristics. Also, this yellow phosphor preferably emits light satisfying 0.414 ≤ cx ≤ 0.453 and 0.532 ≤ cy ≤ 0.558 for the chromaticity coordinates (cx, cy). Thereby, for example, a white light source can be realized in combination with a light-emitting element that emits blue light with a peak wavelength in the range of 430 to 480 nm.
[0056] [Light-emitting module] FIG. 6 is a schematic diagram of a light emitting module according to the present embodiment. The light emitting module 10 according to the present embodiment includes a mounting substrate 12, an LED 14 which is a light emitting element mounted on the mounting substrate 12, and an optical wavelength conversion layer 16 in which a phosphor is dispersed in a resin. The LED 14 emits blue light with a peak wavelength in the range of 430 to 480 nm. The optical wavelength conversion layer 16 includes a fluorescent member in which the yellow phosphor according to the present embodiment is dispersed in a silicone resin transparent to visible light. The optical wavelength conversion layer 16 contains the yellow phosphor at 0.1 to 30 vol % and has a thickness t of 0.01 to 5 mm. The thickness may be in the range of 0.1 to 2 mm. The volume concentration of the yellow phosphor may be 10 vol % or less. This makes it possible to realize a light emitting module in which the desired light emitting efficiency is achieved and the emitted light color has a chromaticity in the range suitable for the headlamp described above.
[0057] The light-emitting characteristics of the white light-emitting modules combining the phosphors of Examples 1, 4, 5, and 7, which were able to obtain yellow light of the desired dominant wavelength, with a blue LED, were evaluated below. Fig. 7 is a diagram for explaining the relationship between the chromaticity of the emitted color of the light-emitting modules according to Examples 11 to 14 and the concentration of the yellow phosphor contained therein.
[0058] Example 11 A light wavelength conversion layer in which the phosphor according to Example 1 (P content 0.40) was mixed in an arbitrary concentration in a transparent silicone resin was potted with a thickness of t=0.5 mm so as to cover the light emission surface of a blue LED with a peak wavelength of 460 nm, to produce a white light emitting module. As a result of evaluating the emission color of a light emitting module with different concentrations of yellow phosphor, the chromaticity of the emission color changed on a straight line connecting the chromaticity of the yellow phosphor and the chromaticity of the blue LED. In the case of the light emitting module according to Example 11, when the concentration of the phosphor according to Example 1 was 3, 4, 5, 6, and 7 vol%, the chromaticity of the emission color of the light emitting module fell within the desired chromaticity range R1 suitable for a headlamp.
[0059] Example 12 A light wavelength conversion layer in which the phosphor according to Example 4 (P content 0.25) was mixed in an arbitrary concentration in a transparent silicone resin was potted with a thickness of t=0.5 mm so as to cover the light emission surface of a blue LED with a peak wavelength of 460 nm, to produce a white light emitting module. As a result of evaluating the emission color of a light emitting module having a different concentration of yellow phosphor, the chromaticity of the emission color changed on a straight line connecting the chromaticity of the yellow phosphor and the chromaticity of the blue LED. In the case of the light emitting module according to Example 12, when the concentration of the phosphor according to Example 4 was 3.5 vol%, the chromaticity of the emission color of the light emitting module fell within the desired chromaticity range R1 suitable for a headlamp.
[0060] (Example 13) A light wavelength conversion layer in which the phosphor according to Example 5 (P content 0.10) was mixed in an arbitrary concentration in a transparent silicone resin was potted with a thickness of t=0.5 mm so as to cover the light emission surface of a blue LED with a peak wavelength of 460 nm, to produce a white light emitting module. As a result of evaluating the emission color of a light emitting module having a different concentration of yellow phosphor, the chromaticity of the emission color changed on a straight line connecting the chromaticity of the yellow phosphor and the chromaticity of the blue LED. In the case of the light emitting module according to Example 13, when the concentration of the phosphor according to Example 4 was 3 vol%, the chromaticity of the emission color of the light emitting module fell within the desired chromaticity range R1 suitable for a headlamp.
[0061] Example 14 A light wavelength conversion layer in which the phosphor according to Example 7 (P content 0.65) was mixed in an arbitrary concentration in a transparent silicone resin was potted with a thickness of t=0.5 mm so as to cover the light emission surface of a blue LED with a peak wavelength of 460 nm, to produce a white light emitting module. As a result of evaluating the emission color of a light emitting module with different concentrations of yellow phosphor, the chromaticity of the emission color changed on a straight line connecting the chromaticity of the yellow phosphor and the chromaticity of the blue LED. In the case of the light emitting module according to Example 14, when the concentration of the phosphor according to Example 4 was 5, 6, and 7 vol%, the chromaticity of the emission color of the light emitting module fell within the desired chromaticity range R1 suitable for a headlamp.
[0062] [Sintered body containing phosphor powder] In the following, a sintered body, which is an example of a fluorescent member containing phosphor powder, which is the powder of the above-mentioned phosphor, will be described. The sintered body may be produced using various known sintering techniques. For example, the phosphor powder may be filled into a mold and molded, and the obtained molded body may be subjected to CIP (Cold Isostatic Pressing) and HIP (Hot Isostatic Pressing), etc., to produce the sintered body.
[0063] The sintered body may contain various materials as necessary in addition to the phosphor powder, for example, a thermally conductive powder, which is a powder of a material having a thermal conductivity higher than that of the phosphor. This material may be, for example, aluminum nitride (AlN), which is a dielectric having a thermal conductivity of about 170 W / mK, or aluminum oxide (Al2O3), which has a thermal conductivity of about 20 W / mK. By containing a thermally conductive powder in addition to the phosphor powder, the sintered body can diffuse the heat generated when the sintered body emits light more quickly than when the sintered body does not contain a thermally conductive powder. According to this embodiment, the heat dissipation property of the sintered body can be improved, so that even when the sintered body is mounted on a high-luminance LED, the temperature rise during light emission can be suppressed, and the deterioration of the light-emitting performance at high temperatures can be suppressed.
[0064] In addition, the volume ratio of the phosphor powder and the thermally conductive powder contained in the sintered body is preferably 90:10 to 60:40. By making the volume ratio of the thermally conductive powder 10 vol% or more and the volume ratio of the phosphor powder 90 vol% or less, the heat dissipation of the sintered body can be further improved. In addition, by making the volume ratio of the thermally conductive powder 40 vol% or less and the volume ratio of the phosphor powder 60 vol% or more, the light absorptance (for example, blue light with a peak wavelength of 450 nm) and light transmittance (for example, yellow light with a wavelength of 550 to 600 nm) of the sintered body can be increased. In this specification, the volume ratio means the volume ratio to the total volume of the phosphor powder and the thermally conductive powder contained in the fluorescent member such as the sintered body.
[0065] The shape of the sintered body is not particularly limited, and the sintered body can be processed into various shapes, but for example, the shape of the sintered body may be a plate shape having a predetermined thickness. Also, the shape of the sintered body may be a shape having a predetermined thickness used as an optical wavelength conversion layer shown in FIG. 6.
[0066] The thickness of the sintered body is not particularly limited, but is preferably 120 to 300 μm (0.12 to 0.30 mm). When the thickness of the sintered body is 120 μm or more, the mechanical strength of the sintered body can be increased. This makes the sintered body less likely to break, and makes the sintered body easier to handle. In addition, when the thickness of the sintered body is 300 μm or less, leakage of light irradiated from the LED to the sintered body from the side surface of the sintered body is suppressed, and the effective luminous flux of the sintered body can be increased.
[0067] The sintered body may transmit light of various wavelengths, for example, light having a wavelength of 550 to 600 nm. The transmittance of the sintered body for light (for example, light having a wavelength of 550 to 600 nm) may be 70% or more. The sintered body (more specifically, the phosphor contained in the sintered body) may absorb light of various wavelengths, for example, blue light having a peak wavelength of 450 nm. The absorptance of the sintered body for blue light may be, for example, 75 to 85%. This allows a light source that emits white light suitable for a desired application (for example, a headlamp) to be realized by combining a light source that emits blue light (for example, an LED) with a fluorescent member. For example, by combining a blue LED with a fluorescent material, it is possible to realize a light source that emits white light with a chromaticity in the range surrounded by chromaticity coordinates (cx, cy) = (0.311, 0.339), (0.313, 0.342), (0.331, 0.354), (0.331, 0.338), (0.319, 0.315), and (0.311, 0.309).
[0068] The sintered body containing the phosphor powder will be described more specifically below using examples.
[0069] Example 15 The phosphor used in the sample according to Example 15 was Ba.0.04 Y 2.91 Al 4.98 P 0.02 O 12 :Ce 3+ 0.05 First, the powder raw materials BaO3 (99.9%), Y2O3 (99.9%), α-Al2O3 (99.99%), AlPO4 (99.99%), and CeO2 (99.99%) were prepared. Then, each powder raw material was weighed out so that the molar ratios were Ba = 0.04, Y = 2.91, Al = 4.98, P = 0.02, and Ce = 0.05.
[0070] BaF2 (99%) was weighed as a flux at 5wt% of the total weight of the powder raw materials, and the BaF2 was added to the weighed powder raw materials, which were then mixed uniformly in a mortar to obtain a mixed powder. The mixed powder was then placed in an alumina crucible (SSA-S B1: manufactured by Nikkato Corporation) and heated and sintered at 1550°C for 4h in a reducing atmosphere (H2:N2 = 5 / 95 (vol ratio)) to obtain a phosphor. The phosphor was then cooled to room temperature and crushed in a mortar to obtain a phosphor powder with a particle size of 1 to 30μm.
[0071] The obtained phosphor powder and AlN powder (99.9%) were weighed out so that the volume ratio was 90: 10. Next, the phosphor powder and AlN powder were mixed and pulverized using a ball mill so that the particle size of these powders was 3 μm or less.
[0072] The powder obtained by mixing and pulverization was filled into a φ20 mm mold and molded at a molding pressure of 10 MPa to obtain a primary molded body. The primary molded body was then compression molded at a molding pressure of 98 MPa using CIP to obtain a secondary molded body. A heating furnace was then used to compress the primary molded body to obtain a 1×10 -3 The secondary compact was heated at 1650°C for 24 hours in a nitrogen atmosphere of 196 MPa. The heated secondary compact was then heated by HIP at 196 MPa and 1550°C for 24 hours to obtain a sintered compact. The obtained sintered compact was then ground and polished with sandpaper to a thickness of 100 μm, and cut into a 1 mm square to prepare a plate-shaped sintered compact sample.
[0073] The thermal conductivity of the samples was measured by a steady-state method using a thermal conductivity meter. The standard value of thermal conductivity was set to 30 W / mK, and if the measured value was equal to or higher than this standard value, the thermal conductivity of the sample was evaluated as good.
[0074] The transmittance of the sample was measured using a spectrophotometer (Hitachi). The wavelength of the excitation light was 460 nm, and the measurement light was yellow light with a wavelength of 600 nm. When the transmittance of the yellow light was 70% or more, the transmittance of the sample was evaluated as good.
[0075] The absorptance of the sample was measured using an integrating sphere. The excitation light was blue light with a wavelength of 460 nm. When the absorptance of blue light was 75% to 85%, the absorptance of the sample was evaluated as good.
[0076] In addition, the effective luminous flux of the sample was measured using an illuminometer. Specifically, a plate-shaped sample was mounted on an LED chip that emits 460 nm excitation light, and the LED chip was made to emit excitation light, and measurements were taken only directly above and on the sides of the sample, and the effective luminous flux was calculated. When the amount of light leaking from the sides of the sample was 10% or less, the effective luminous flux of the sample was evaluated as good.
[0077] Furthermore, if the sample was not damaged when handled with tweezers, the handleability of the sample was evaluated as being good.
[0078] Furthermore, when the thermal conductivity, transmittance, absorptance, ease of handling, and effective luminous flux of a sample were all evaluated as good, the overall evaluation of the sample was determined to be good.
[0079] Table 2 shows the preparation conditions and evaluation results of the samples according to the respective examples.
[0080] [Table 2]
[0081] (Examples 16 to 20) In Examples 16 to 20, sintered body samples were produced in the same manner as in Example 15, except that the thickness of the sample was changed to 120, 180, 240, 300, or 360 μm.
[0082] (Examples 21 to 38) In Examples 21 to 38, sintered body samples were produced in the same manner as in Example 15, except that the volume ratio of the phosphor powder to the AlN powder and the thickness of the sample were changed to the values shown in Table 2. Specifically, the volume ratio of the phosphor powder to the AlN powder was set to 70:30, 60:40, or 50:50, and for each volume ratio, the thickness of the sample was set to 100, 120, 180, 240, 300, or 360 μm, and sintered body samples were produced.
[0083] (Example 39) In Example 39, the mixed powder was heated and sintered in the same manner as in Example 15, and the resulting phosphor was pulverized in a mortar to obtain a phosphor powder. This phosphor powder was not mixed with AlN powder, but was pulverized using a ball mill.
[0084] Next, the phosphor powder pulverized using a ball mill was filled into a die having a diameter of 20 mm, and the phosphor powder was molded under a molding pressure of 10 MPa to obtain a primary molded body. Thereafter, a sample of a sintered body was prepared in the same manner as in Example 15.
[0085] (Example 40) In Example 40, a sintered body sample was prepared in the same manner as in Example 23, except that Al2O3 powder was mixed into the phosphor powder instead of AlN powder, i.e., the volume ratio of the phosphor powder to the thermal conductive powder was 70:30, and the sample thickness was 180 μm.
[0086] The method for producing the samples according to the examples has been described above. The evaluation results will now be described.
[0087] The thermal conductivity of the samples containing AlN powder according to Examples 15 to 38 all exceeded the reference value and were good. Furthermore, in the examples in which the volume fraction of the AlN powder was 10 to 40 vol% and the thickness of the sample was 120 to 300 μm, the thermal conductivity, transmittance, absorptance, handling properties, and effective luminous flux were all good. The evaluation results are described in more detail below.
[0088] In the sample of Example 39 that does not contain the thermally conductive powder, the transmittance, absorptance, handling, and effective luminous flux were evaluated as good, but the thermal conductivity was not evaluated as good. The sample of Example 40 contains Al2O3 powder, which has a thermal conductivity higher than that of the phosphor. Therefore, the thermal conductivity of the sample of Example 40 was higher than that of the sample of Example 39, but was not evaluated as good.
[0089] In the sample according to Example 23, the thermally conductive powder is changed from Al2O3 powder to AlN powder, as compared with the sample according to Example 40. Since the thermal conductivity of AlN is higher than that of Al2O3, the thermal conductivity of the sample according to Example 23 is higher than that of Example 40, and is a good value.
[0090] Furthermore, the thermal conductivity of all of the samples according to Examples 15 to 38 containing AlN powder was good (>30 W / mK). Therefore, it was found that the thermal conductivity of the sample was good if the volume fraction of the AlN powder was at least 10 vol% or more.
[0091] Furthermore, among Examples 21 to 38 in which the volume fraction of AlN powder was 30 vol% or more, the transmittance was less than 70% in the Examples in which the sample thickness was 360 μm, but the transmittance was good in the Examples in which the sample thickness was 300 μm or less.
[0092] Furthermore, among Examples 33 to 38 in which the volume fraction of the AlN powder is 50 vol%, the examples in which the thickness of the sample is 100 to 300 μm have an absorptivity of less than 75%, but the examples in which the thickness is 360 μm have good absorptivity results. Note that, in the examples in which the thickness is 100 to 300 μm, light leakage from the side surface of the sample can be suppressed, and good results are obtained for the effective luminous flux.
[0093] Furthermore, in examples in which the sample thickness was less than 120 μm, the mechanical strength was low and good results were not obtained in terms of handleability, but in examples in which the sample thickness was 120 μm or more, the sample did not break even when handled with tweezers, and good results were obtained in terms of handleability.
[0094] [Light emitting module] (Example 41) In Example 41, the light-emitting module described with reference to Fig. 6 was produced. Specifically, a sintered body containing phosphor powder and AlN powder produced under the same conditions as the sample of Example 22 was used as an optical wavelength conversion layer, and the optical wavelength conversion layer was room-temperature bonded to a sapphire mounting substrate so that the optical wavelength conversion layer covered the light emission surface of a blue LED (peak wavelength: 460 nm), thereby producing a white light-emitting module.
[0095] In Example 41, the chromaticity of the emitted color of the light emitting module was within the chromaticity range suitable for headlamps, with chromaticity (cx, cy) = (0.32, 0.33). Therefore, in this Example, it can be said that by mounting the fluorescent member according to one embodiment of the present invention on a blue LED, a white LED having excellent high-temperature characteristics and suitable for specific applications (such as vehicle headlamps) was fabricated.
[0096] Although the present invention has been described above with reference to the above-mentioned embodiment and each example, the present invention is not limited to the above-mentioned embodiment and each example, and suitable combinations and substitutions of the configurations of the embodiment and each example are also included in the present invention. In addition, it is possible to suitably rearrange the combinations and processing order in the embodiment and each example based on the knowledge of a person skilled in the art, and to add modifications such as various design changes to the embodiment and each example, and the embodiment with such modifications can also be included in the scope of the present invention.
[0097] In the above embodiment, the sintered body is described as an example of the fluorescent member containing the phosphor powder and the thermally conductive powder. However, the fluorescent member is not limited to this, and may be, for example, a resin in which the phosphor powder and the thermally conductive powder are dispersed. [Explanation of symbols]
[0098] 10 light emitting module, 12 mounting board, 14 LED, 16 light wavelength conversion layer.
Claims
1. The general formula is M a Y 3-a-b A 5-a/2 P a/2 O 12 : Ce b (wherein M represents at least one element selected from the group consisting of Ba, Sr, Ca, and Mg; a satisfies 0<a≦1.5, and b satisfies 0<b≦0.12).
2. 2. The phosphor according to claim 1, which has a garnet-type crystal structure.
3. 3. The phosphor according to claim 1, which is excited by blue light having a peak wavelength in the range of 430 to 480 nm and emits yellow light having a dominant wavelength in the range of 567 to 572 nm.
4. The phosphor according to any one of claims 1 to 3, characterized in that it is excited by blue light having a peak wavelength in the range of 430 to 480 nm and emits light whose chromaticity coordinates (cx, cy) satisfy 0.414≦cx≦0.453 and 0.532≦cy≦0.
558.
5. A phosphor powder which is a powder of the phosphor according to any one of claims 1 to 4; a thermally conductive powder, which is a powder of a material having a thermal conductivity higher than that of the phosphor; A fluorescent member comprising:
6. 6. The fluorescent member according to claim 5, wherein a volume ratio of the phosphor powder to the thermally conductive powder is 90:10 to 60:
40.
7. The phosphor powder absorbs light having a peak wavelength of 450 nm, The thickness of the fluorescent member is 0.12 to 0.30 mm.
7. The fluorescent member according to claim 5, wherein the transmittance of the fluorescent member for light having a wavelength of 550 to 600 nm is 70% or more.
8. The phosphor powder absorbs blue light having a peak wavelength of 450 nm, 8. The fluorescent member according to claim 5, wherein the absorptance of the blue light of the fluorescent member is 75 to 85%.
9. A fluorescent member comprising a resin transparent to visible light and the phosphor according to claim 1 encapsulated in the resin, The phosphor is contained in the resin at 0.1 to 30 vol %; The fluorescent member has a thickness of 0.01 to 5 mm.
10. an LED that emits blue light with a peak wavelength in the range of 430 to 480 nm; and a light wavelength conversion layer including the fluorescent member according to claim 5 , which is excited by the blue light emitted by the LED and emits yellow light, A light-emitting module, characterized in that the emitted light color obtained by mixing the blue light and the yellow light has a chromaticity in the range surrounded by chromaticity coordinates (cx, cy) = (0.311, 0.339), (0.313, 0.342), (0.331, 0.354), (0.331, 0.338), (0.319, 0.315), and (0.311, 0.309).
Citation Information
Patent Citations
Phosphorous silicate fluorescent powder and preparation method thereof
CN102329617A
Yttrium-barium phosphate fluorescent powder doped by cerium ions and preparation method thereof
CN105131955A
Green-emitting, garnet-based phosphors for general and backlighting applications
JP2015180741A